2006
DOI: 10.1038/sj.jp.7211621
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester placental location as a predictor of an adverse pregnancy outcome

Abstract: Objective: To determine if the second trimester placental location is associated with perinatal outcomes. Materials and methods:Observational study of placental location and the subsequent risk of an adverse pregnancy outcome. Placental location was divided into three categories, low, high lateral and high fundal.Results: There were 3336 pregnancies analyzed in this study. Low implantation sites had a greater risk of preterm labor (odds ratio (OR) 1.70, 95% confidence interval (CI) 1.38 to 2.90, P<0.001), pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
70
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 9 publications
9
70
1
2
Order By: Relevance
“…Fetal outcome in terms of gestational age, birth weight, APGAR at 1 and 5 minutes was almost similar in both the groups. Fetal outcome in terms of weight was AGA in 86 cases, SGA in 30 cases and LGA in 9 cases and results were in accordance with the study of Liberti et al, 8 Anuja V Bhalerao 9 Magann et al, 10 Devaranjan et al 11 and Elena contro et al 12 CONCLUSION: Prediction of preeclampsia by second trimester USG guided placental localization is simple, cheap, noninvasive, safe and effective screening method. Laterally situated placenta is associated with high risk of development of PIH.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Fetal outcome in terms of gestational age, birth weight, APGAR at 1 and 5 minutes was almost similar in both the groups. Fetal outcome in terms of weight was AGA in 86 cases, SGA in 30 cases and LGA in 9 cases and results were in accordance with the study of Liberti et al, 8 Anuja V Bhalerao 9 Magann et al, 10 Devaranjan et al 11 and Elena contro et al 12 CONCLUSION: Prediction of preeclampsia by second trimester USG guided placental localization is simple, cheap, noninvasive, safe and effective screening method. Laterally situated placenta is associated with high risk of development of PIH.…”
Section: Discussionsupporting
confidence: 79%
“…It is statistically significant (p value <0.001). Many of the other authors like Pai M et al, 1 Patel A et al, 2 Liberti et al, 8 Bhalerao et al, 9 Magann et al, 10 Kartika Devrajan et al, 11 also suggested that central placenta is more common. However various other studies found lateral placenta to be more common like Kofinas et al, 5 Liberti et al, 8 kakkar, and Elena contro et al 12 These differences may be due to differences in criteria defining central and lateral placenta.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, asymmetric blood flow may be related to regional heterogeneity in the transformation of spiral arteries into low-resistance vessels (17). Other investigators have shown that when the placenta is laterally placed, volumetric flow is higher and vascular impedance lower in the ipsilateral UA and that there is an increased incidence of PE, fetal distress, Cesarean sections, and IUGR (8,19,22). Because we did not observe differences in the location of the placenta among groups or any relationship between placental location and Q UA , we concluded that altered trophoblast invasion and remodeling rather than placenta location was responsible for the asymmetry observed.…”
Section: Discussionmentioning
confidence: 99%
“…Placental location has been implicated in preterm birth, in fetal mal-position and malpresentation, small for gestational age, low Apgar score and in development of pre-eclampsia. [1][2][3][4] The significance of placental location in the uterine cavity has been studied extensively. Placental location has been found to correlate with fetal position and presentation, length of gestation, course of labour, presence of pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%